2014
DOI: 10.1186/ar4591
|View full text |Cite
|
Sign up to set email alerts
|

Targeting pro-inflammatory cytokines following joint injury: acute intra-articular inhibition of interleukin-1 following knee injury prevents post-traumatic arthritis

Abstract: IntroductionPost-traumatic arthritis (PTA) is a progressive, degenerative response to joint injury, such as articular fracture. The pro-inflammatory cytokines, interleukin 1(IL-1) and tumor necrosis factor alpha (TNF-α), are acutely elevated following joint injury and remain elevated for prolonged periods post-injury. To investigate the role of local and systemic inflammation in the development of post-traumatic arthritis, we targeted both the initial acute local inflammatory response and a prolonged 4 week sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
151
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 71 publications
3
151
0
Order By: Relevance
“…Inflammation is one key factor in bone wasting, and IL-1, TNFa, and other cytokines have been implicated in its aetiology [3,22,44,52]. After joint surgery and in general, it is important to control synovitis [11,12,19,36] in order to resolve (post-traumatic) joint inflammation rapidly. Treatment of inflammation with common NSAIDs does not specifically address the underlying pathways, and excessive NSAID use may interfere with the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is one key factor in bone wasting, and IL-1, TNFa, and other cytokines have been implicated in its aetiology [3,22,44,52]. After joint surgery and in general, it is important to control synovitis [11,12,19,36] in order to resolve (post-traumatic) joint inflammation rapidly. Treatment of inflammation with common NSAIDs does not specifically address the underlying pathways, and excessive NSAID use may interfere with the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Before drawing conclusions regarding the role of these proteases in the development of posttraumatic OA, these patients will need to be followed over time to evaluate if these MMPs and aggrecan degradation are more strongly correlated with the ultimate development of posttraumatic OA. Prior studies have suggested various cell-signaling mechanisms that may play a role in the development of posttraumatic OA including transforming growth factor-b, endothelin-1, interleukin-1b, and NF-jB [12,15,22,33,37,38]. Our current study should draw attention to the postinjury presence of MMPs and aggrecan degradation as potentially playing a role in progression to OA as well.…”
Section: Discussionmentioning
confidence: 99%
“…Also in murine models of inflammatory arthritis and posttraumatic osteoarthritis, no effect on cartilage destruction upon TNFa blockade has been found, corroborating this hypothesis. [36][37][38] Nevertheless, this study does not exclude a role for TNFa in inducing the reversible (short-term) changes to cartilage.…”
Section: 28mentioning
confidence: 93%
“…35 In experimental arthritis, blocking IL-1 prevents cartilage damage upon inflammation 36,37 as is also observed in a posttraumatic osteoarthritis model. 38 Therapeutic efficacy of IL-1RA is demonstrated in hand osteoarthritis 39 and in 2 cases suffering from another form of ironinduced arthropathy in case of hemochromatosis. 40 Opposing IL-1 was most effective when performed within 8 hours after blood exposure, but benefit was still achieved when performed until 24 hours after exposure to blood.…”
Section: 28mentioning
confidence: 99%